Nitrogen sources differentially affect respiration, growth, and carbon allocation in Andean and Lowland ecotypes of Chenopodium quinoa Willd - Jerez, María Paz; Ortiz, José; Castro, Catalina; Escobar, Elizabeth; Sanhueza, Carolina; Del-Saz, Néstor Fernández; Ribas-Carbo, Miquel; Coba de la Peña, Teodoro; Ostria-Gallardo, Enrique; Fischer, Susana; Castro, Patricio Alejandro; Bascunan-Godoy, Luisa (Frontiers in Plant Science, 2023)
Chenopodium quinoa Willd is a native species of origin in the High Andes plateau (Altiplano) and its cultivation has been spread out to the south of Chile. Because of the different edaphoclimatic characteristics of both regions, more nitrate (NO3-) is accumulated in soils from Altiplano that in the south of Chile, where soils favor ammonium accumulation (NH4+). To elucidate whether C. quinoa ecotypes differ in several physiological and biochemical parameters related to their capacity to assimilate NO3- and NH4+, juvenile plants of Socaire (from Altiplano) and Faro (from Lowland/South of Chile) were grown under different sources of N (NO3- or NH4+). Measurements of photosynthesis and foliar oxygen-isotope fractionation were carried out, together with classical biochemical analysis to study C : N relationship. Overall, we observed higher biomass productivity of Faro grown under NH4+, probably due to respiratory plasticity that allowed increases in cytochrome oxidase activity and ATP production, promoting the protein production from assimilated NH4+, contributing to growth. We conclude that this different sensitivity for NH4+ between quinoa ecotypes may contribute to a better understanding of nutritional aspects driving plant primary productivity in quinoa.